THE RELATION BETWEEN POSITIVE PSYCHOLOGICAL CAPITAL AND INDIVIDUAL PERFORMANCE: THE SAMPLE OF THE CENTRAL UNION OF TURKISH AGRICULTURAL CREDIT COOPERATIVES (Third Sector Social Economic Review, 2015)
The purpose of this study is to find out the elements of positive pschological capital’s relation with the personel performance.150 agricultural credit cooperatives union employees constitute the sample of the study. The research, collected data through survey method, positive pschological capital scale and personel performance scale was used. The datas were subjected to analys by the helps of SPSS (20.0) programme. Then Pearson correlation was calculated to state between relationships both depended and independent variables. These correlations were calculated seperately fort he own dimensions scales and all dimensions among the scale.As a result of the correlation, there is not a strong relation determined between positive psychological capital and individual performance. It has been looked seperately at relationship between optimisim, reresiliency, hope, self efficacy which are subbranches of positive psyhological capital and individual performance. To measure whether the demographic variables (age, working time at company, the position at company, gender and education level) differentiates dependent and indepented variable or not, one-way ANOVA and t_test was applied. Consequently, It became obvious that demographic variables did not change the sub dimensions of positive pschological capital and the individual performance.
Keywords: Pozitif Psikolojik Sermaye; Bireysel Performans